The contribution of sustainability practices and microfinance on micro-enterprise business performance in Malaysia: the moderating role of business location / Noorul Hafizah Hashim, Hisham Mohammad and Md. Mahmudul Alam - Hashim, Noorul Hafizah; Mohammad, Hisham; Alam, Md. Mahmudul (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
This study aimed to examine the impact of sustainability practices (SP) and microfinance (MF) on the financial performance (FP) and non-financial performance (NFP) of micro-enterprises in Malaysia. This study also introduced business location as a moderating variable in the model. A cross-sectional research design using a quantitative research approach was adopted. The data were collected from the owners/managers of micro-enterprises of provision stores in retail sectors covering 12 districts in Kedah. Total 300 self-administrated questionnaires were distributed to micro-enterprise owners/managers, and 282 were utilised for further analysis. Data were further analysed using SPSS and SmartPLS 4 software through the structural equation technique. The results showed a significant direct effect of SP and MF on the FP and NFP of micro-enterprises. Meanwhile, business location significantly moderated the relationship between SP, MF and NFP but not FP of micro-enterprises. This study is the first in examining business location as a moderator on the relationship between SP, MF, FP and NFP in a single model. The findings from this study would enrich the current literature on RBV theories by incorporating SP and MF in the context. Furthermore, this study could also contribute to the government and microfinance institutions designing or strengthening the microfinance programs, infrastructure and guidelines, particularly in improving the overall business performance of MSMEs.